2015
DOI: 10.21082/jpptp.v34n2.2015.p153-163
|View full text |Cite
|
Sign up to set email alerts
|

Respon Varietas Unggul Kacang Tanah terhadap Cekaman Salinitas Responses of Groundnut Varieties to Salinity Stress

Abstract: <p>Soil salinity has negative effect on crop growth and crop productivity. Information on the response of groundnut varieties to salinity is required for varietal selection adaptable to saline  soil condition. The research was conducted at the greenhouse of Indonesian Legume and Tuber Crops Research Institute (Iletri), Malang, East Java from July to September 2013. The objective of the research was to study the effect of salinity on groundnut growth.<br />Ten groundnut varieties, consisted of seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…Salinity tolerance of groundnut varied among genotypes (Singh et al 2007;Singh et al 2008). Taufiq et al (2015) found that pod yield of 10 cultivars decreased by 30-53% at salinity of 1.60-1.84 dS/m and by 59-93% at salinity of 2.95-4.44 dS/m compared to the control.At low salinity level, planting tolerant cultivar is more efficient than amelioration. However, amelioration is needed if the salinity above the level that can be tolerated by crop.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Salinity tolerance of groundnut varied among genotypes (Singh et al 2007;Singh et al 2008). Taufiq et al (2015) found that pod yield of 10 cultivars decreased by 30-53% at salinity of 1.60-1.84 dS/m and by 59-93% at salinity of 2.95-4.44 dS/m compared to the control.At low salinity level, planting tolerant cultivar is more efficient than amelioration. However, amelioration is needed if the salinity above the level that can be tolerated by crop.…”
Section: Introductionmentioning
confidence: 86%
“…Soil EC during the trial was >11 dS/m, and it was above the critical level of 3.2 dS/m (Yadav et al, 2011). In pot experiment, groundnut could not perform pod on soil EC 6.5 dS/m (Mungala et al, 2008), on soil EC >1.84 dS/m (Taufiq et al, 2015). On field experiment with soil EC 15.33 dS/m, groundnut of Domba and Hypoma-1 cultivar produced 0.5-0.7 t/ha dry pod (Taufiq et al, 2016).…”
Section: Soil Properties and Nutrient Uptakementioning
confidence: 99%
“…Yadav et al (2011) found that EC 3.2 dS/m is critical value for groundnut based on yield reduction. From greenhouse trial showed that ten Indonesian groundnut varieties tested failed to produce pod on soil with EC about 2.0 dS/m (Taufiq et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Salinitas juga mengakibatkan ketidakseimbangan hara dan toksisitas ion sehingga gejala yang muncul pada kedelai adalah daun menguning (klorosis), seperti terbakar di bagian tepi, layu, kering, dan kemudian gugur. Taufiq et al (2015) melaporkan hal yang sama pada kacang tanah dengan perlakuan salinitas. Daun kacang tanah menguning, mengering kemudian gugur yang merupakan indikasi gejala keracunan garam.…”
Section: Populasi Tanamanunclassified
“…Unsur N dan Mg 2+ merupakan komponen pembentuk klorofil yang berperan dalam fotosintesis, sehingga penurunan serapan unsur-unsur tersebut mengakibatkan pembentukan klorofil terganggu dan fotosintesis terhambat. Cekaman salinitas juga dilaporkan memicu reaksi foto oksidatif yang merusak membran tilakoid kloroplas (Anitha dan Usha 2012, Subramanyam et al 2012, Aini et al 2014, Taufiq et al 2015.…”
Section: Indeks Kandungan Klorofil Daununclassified